THE EDUCATIONAL MANAGEMENT - SOCIAL NETWORKING AND EFFECT OF GLOBALIZATION: POSITIVE & NEGATIVE - Askarovna, Toshpulatova Ismigul (PT. Antis International Publisher, 2024)
This article is written about the global social network system and the impact of the globalization process on the education management system. Because, during the pandemic, in all countries of the world, especially in my country where I live, the educational management process was transferred to the online system, and the globalization process also began to accelerate compared to previous years.